Expansion of the geographic range of the eucalypt pest Paropsisterna cloelia (Stål) (Coleoptera: Chrysomelidae) through synonymy and invasion. Issue 3 (9th June 2020) - Nahrung, Helen F; Lewis, Aymee S R; Ridenbaugh, Ryan D; Allen, Geoff R; Reid, Chris A M; McDougal, Rebecca L; Withers, Toni M
Abstract: The accidental introduction of the eucalypt‐feeding paropsine beetle Paropsisterna cloelia ( Paropsisterna variicollis ) into New Zealand (NZ) in 2016 prompted investigation of the species complex to which the invasive species belongs. Two mitochondrial gene regions, Cytochrome c oxidase subunit 1 and Cytochrome b, were sequenced from field‐collected specimens superficially resembling P. cloelia collected in Queensland, the Australian Capital Territory, New South Wales, Victoria, South Australia, Tasmania, Western Australia (WA) and NZ. Four distinct Paropsisterna species groups were found, and representatives from each clade were identified with named species using morphology. P. cloelia was confirmed via sequencing and morphology to occur in all sampled geographic regions. The WA and NZ populations showed no diversity at the gene regions studied and hence represent invasive populations. The invasive WA haplotype was shared with both Tasmania and Victoria, whereas the NZ haplotype was unique, but most similar to one shared between WA, Tasmania and Victoria. The melanistic colour variant of P. cloelia was only found in eastern mainland Australian populations and was absent from Tasmania and invasive populations. Implications for pest management, including biological control, are discussed.